Improving Learning Outcomes in Natural Sciences (IPA) for Grade VI Students MIN 2 Bulukumba through the Problem Based Learning model - fattah, abdul (MACCA : Science-Edu Journal, 2024)
This class action research aims to find out the steps of applying the Problem Based Learning Model. The subjects of this study were students of class VI MIN 2 Bulukumba in the odd semester of the 2022/2023 school year, totaling 21 people. This research consists of 2 cycles, each cycle includes stages: planning, action, observation, evaluation and reflection. Cycle I was carried out three times a meeting and cycle II was carried out three times a meeting. Data collection was carried out through observation of each learning process and analyzed by descriptive analysis. The application of the Problem Based Learning (PBL) Model goes through the following steps: 1) Orient students to the problem, 2) Organizing students to learn, 3) Guiding individual and group investigations, 4) Developing and presenting work, 5) Analyzing and evaluating the problem solving process. In cycle I, the average score of students' learning outcomes was 77.73 which was in the high completion category, in cycle II it was 84.93 which was in the very high completion category, while the learning outcomes of students obtained in cycle I were 60% and cycle II was 63.33%. This shows that there was an increase of 21.33%.